All Days 2008
DOI: 10.2118/117836-ms
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Water Injection Improves Oil Production in Carbonate Reservoir

Abstract: The cyclic injection process to improve water flooding in carbonate reservoir was evaluated in laboratory experiments, as well as analytical and numerical simulations. Laboratory cyclic injection experiments were performed on a carbonate rock sample with an artificial horizontal fissure. Live oil was established by in-situ recombination of dead oil with hydrocarbon gas at reservoir temperature and bubble point pressure. The experiments were designed by numerical simulation of the cyclic proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The recovery performance of cyclic water flooding in conventional reservoirs has been demonstrated by lots of experimental and simulation studies as well as field practice reports (Li et al, 1995;Stirpe et al, 2004;Shchipanov et al, 2008;Surguchev et al, 2008). The concept of such cyclic injection is based on (1) pulsed injection and (2) alternating waterflood patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The recovery performance of cyclic water flooding in conventional reservoirs has been demonstrated by lots of experimental and simulation studies as well as field practice reports (Li et al, 1995;Stirpe et al, 2004;Shchipanov et al, 2008;Surguchev et al, 2008). The concept of such cyclic injection is based on (1) pulsed injection and (2) alternating waterflood patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Former study considered down dip water injection and up dip gas injection to improve the displacement efficiency, however it has been shown that up dip water injection and down dip gas injection are suitable for the reservoir with high permeable layer on top or for the reservoir with thin oil rim layer. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] III. METHODOLOGY…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cyclic water flooding is mostly better than conventional water flooding, typically 1%-10% higher in oil recovery. The main characteristics of cyclic water flooding are as follows: (1) the increase in recovery rate decreases as the degree of water flooding deepens; (2) if the heterogeneity for the reservoir is strong, the effect of the cyclic water flooding is important; (3) the earlier the cyclic water flooding, the higher increase in oil recovery [24,25].…”
Section: Introductionmentioning
confidence: 99%